NMR metabolomics revealed metabolites and bioactivity variation in Torbangun leaves Plectranthus amboinicus L. with different origins - Nancy Dewi Yuliana; Muhammad Anwari Sugiharto; Hanifah Nuryani Lioe; Masao Goto; Yuko Takano Ishikawa (Indonesian Journal of Biotechnology, 2018)
Plectranthus amboinicus has been reported to have antidiabetic and antioxidant activities. Environmental factors might influence the plant’s secondary metabolite profile and its beneficial properties. NMR-based metabolomics was used to show phytochemical variations between specimens of P. amboinicus grown in Japan and Indonesia. The results showed that flavonoids and triterpenes were among the discriminating factors of the variation between the two groups. Targeted comparative analysis of the concentration of the specific flavonoids of the plants using a validated HPLC-MWD method showed that the Japanese samples contained a higher concentration of total flavonoids compared with the Indonesian samples. The Japanese and Indonesian samples contained 1100.6 ± 5.1 and 532.4 ± 1.8 µg/g luteolin, and 584.5 ± 7.4 and 571.7 ± 11.6 µg/g apigenin, respectively. Eriodyctiol was detected only in the Indonesian samples. Contrarily, more intensive DPPH reduction and α-glucosidase inhibition activities were found in the Indonesian samples (IC50 14.4 ± 1.2 and 24.0 ± 0.3 µg/mL for the DPPH assay, 1181.9 ± 113.5 and 4451.4 ± 290.0 µg/mL for α-glucosidase inhibition, respectively). Thus, flavonoids might not be the only group of compounds related to the aforementioned bioactivities. This should be confirmed by further research targeting other groups of compounds, such as triterpenes.